Islamic perspectives on HIV: a scoping review - Abier Hamidi; Pramod Regmi; Edwin van Teijlingen (Springer, 2024)
Abstract Background There is some evidence to suggest that the human immunodeficiency virus (HIV) prevalence may be lower in Muslim-majority countries and among Muslims in general. The low prevalence is usually accredited to Islam's influence on the behaviours that affect transmission of HIV. Reports of HIV epidemics, predominately among injection drug users (IDUs), are emerging in Muslim-majority countries, forcing the Muslim world to respond to them. Objective This study is a scoping review of the literature that addresses (a) the messages communicated regarding HIV from an Islamic perspective, (b) the approaches Muslims adopt to comprehend and treat people living with HIV, and (c) roles of Islam and religious leaders. This review scopes the available literature and identifies the nature and extent of research conducted to date. Methods A comprehensive search was performed using PubMed, Medline, Web of Science, ScienceDirect, Scopus, and Academic Search Ultimate. Primary research that focused on the Islamic perspective and discourse of HIV and AIDS, were considered. In total 22 studies dating from 2002 to 2017 studies were included. Findings. Five themes emerged (1) Western Import, (2) God's Wrath, (3) God's Test, (4) Tolerance and Mercy, and (5) Religious Silence. Conclusion HIV has indiscriminately affected communities globally and the Muslim community has not been an exception. More diverse research is required as well as Muslim- majority countries and communities must develop effective HIV awareness and prevention campaigns that are rooted in Islamic teachings and involve religious leaders.